2022
DOI: 10.1177/11786302221129955
|View full text |Cite
|
Sign up to set email alerts
|

“I Can Sense When My Hands Need Washing”: A Qualitative Study and Thematic Analysis of Factors Affecting Young Adults’ Hand Hygiene

Abstract: Handwashing is one of the most effective and low-cost public health measures. However, it is often not practiced frequently enough or correctly by the public. Young adults in particular have poorer intentions to wash their hands, frequency of handwashing, and sanitizer use compared to other age groups. Therefore, there is a need to identify barriers and facilitators affecting hand hygiene within this group. The objective of this qualitative study was to apply the Theoretical Domains Framework to explore factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Various studies claimed that the availability of handwashing facilities was positively associated with effective handwashing practices. 44 , 45 Hence, determining the availability of handwashing facilities and factors affecting their presence would support the installation of handwashing facilities, thereby playing a role in reducing the spread of infectious diseases that could be prevented through effective handwashing practices. 42 Findings obtained from this study also indicated that various factors were associated with the presence of handwashing facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies claimed that the availability of handwashing facilities was positively associated with effective handwashing practices. 44 , 45 Hence, determining the availability of handwashing facilities and factors affecting their presence would support the installation of handwashing facilities, thereby playing a role in reducing the spread of infectious diseases that could be prevented through effective handwashing practices. 42 Findings obtained from this study also indicated that various factors were associated with the presence of handwashing facilities.…”
Section: Discussionmentioning
confidence: 99%